Nociceptor-localized cGMP-dependent protein kinase I is a critical generator for central sensitization and neuropathic pain. Issue 1 (January 2021) - Wang, Fei; Ma, Sui-Bin; Tian, Zhi-Cheng; Cui, Ya-Ting; Cong, Xiang-Yu; Wu, Wen-Bin; Wang, Fu-Dong; Li, Zhen-Zhen; Han, Wen-Juan; Wang, Tao-Zhi; Sun, Zhi-Chuan; Zhang, Fan-Liang; et al.
Abstract : Abstract: Patients with neuropathic pain often experience exaggerated pain and anxiety. Central sensitization has been linked with the maintenance of neuropathic pain and may become an autonomous pain generator. Conversely, emerging evidence accumulated that central sensitization is initiated and maintained by ongoing nociceptive primary afferent inputs. However, it remains elusive what mechanisms underlie this phenomenon and which peripheral candidate contributes to central sensitization that accounts for pain hypersensitivity and pain-related anxiety. Previous studies have implicated peripherally localized cGMP-dependent protein kinase I (PKG-I) in plasticity of nociceptors and spinal synaptic transmission as well as inflammatory hyperalgesia. However, whether peripheral PKG-I contributes to cortical plasticity and hence maintains nerve injury–induced pain hypersensitivity and anxiety is unknown. Here, we demonstrated significant upregulation of PKG-I in ipsilateral L3 dorsal root ganglia (DRG), no change in L4 DRG, and downregulation in L5 DRG upon spared nerve injury. Genetic ablation of PKG-I specifically in nociceptors or post-treatment with intervertebral foramen injection of PKG-I antagonist, KT5823, attenuated the development and maintenance of spared nerve injury–induced bilateral pain hypersensitivity and anxiety. Mechanistic analysis revealed that activation of PKG-I in nociceptors is responsible for synaptic potentiation in the anterior cingulate cortex upon peripheral neuropathy through presynaptic mechanisms involving brain-derived neurotropic factor signaling. Our results revealed that PKG-I expressed in nociceptors is a key determinant for cingulate synaptic plasticity after nerve injury, which contributes to the maintenance of pain hypersensitivity and anxiety. Thereby, this study presents a strong basis for opening up a novel therapeutic target, PKG-I, in nociceptors for treatment of comorbidity of neuropathic pain and anxiety with least side effects. Abstract : Supplemental Digital Content is Available in the Text.Peripherally localized cGMP-dependent protein kinase I in nociceptors triggers cingulate synaptic plasticity and comorbidity of neuropathic pain and anxiety.